Harold Macmillan and Britain’s World Role
XV, 161 p.
Keywords: When Harold Macmillan became prime minister in 1957, Britain had reached a critical point in its contemporary history. There was still evidence of Britain's status as a great power, yet the previous year's humiliation at Suez had undermined its credibility. By taking key areas of overseas policy - summitry, the Middle East, defence, Empire, and Europe - this volume looks at Macmillan's attempts to establish a new foreign policy agenda after Suez. Based on research in public and private archives in Britain, America and Germany, Harold Macmillan and Britain's World Role offers a critical reappraisal of British foreign policy between 1957 and 1963, addressing how successfully Macmillan answered his own key question: 'Why should the UK stay in the big game?'.